Impaired Right Ventricular Hemodynamics Indicate Preclinical Pulmonary Hypertension in Patients With Metabolic Syndrome. Issue 3 (10th March 2015) - Gopal, Deepa M.; Santhanakrishnan, Rajalakshmi; Wang, Yi‐Chih; Ayalon, Nir; Donohue, Courtney; Rahban, Youssef; Perez, Alejandro J.; Downing, Jill; Liang, Chang‐seng; Gokce, Noyan; Colucci, Wilson S.; Ho, Jennifer E.
Abstract : Background: Metabolic disease can lead to intrinsic pulmonary hypertension in experimental models. The contributions of metabolic syndrome (MetS) and obesity to pulmonary hypertension and right ventricular dysfunction in humans remain unclear. We investigated the association of MetS and obesity with right ventricular structure and function in patients without cardiovascular disease. Methods and Results: A total of 156 patients with MetS (mean age 44 years, 71% women, mean body mass index 40 kg/m 2 ), 45 similarly obese persons without MetS, and 45 nonobese controls underwent echocardiography, including pulsed wave Doppler measurement of pulmonary artery acceleration time (PAAT) and ejection time. Pulmonary artery systolic pressure was estimated from PAAT using validated equations. MetS was associated with lower tricuspid valve e′ (right ventricular diastolic function parameter), shorter PAAT, shorter ejection time, and larger pulmonary artery diameter compared with controls ( P <0.05 for all). Estimated pulmonary artery systolic pressure based on PAAT was 42±12 mm Hg in participants with MetS compared with 32±9 and 32±10 mm Hg in obese and nonobese controls ( P for ANOVA <0.0001). After adjustment for age, sex, hypertension, diabetes, body mass index, and triglycerides, MetS remained associated with a 20‐ms–shorter PAAT (β=−20.4, SE=6.5, P =0.002 versus obese). This association persisted after accounting for left ventricular structure and function and after exclusion of participants with obstructive sleep apnea. Conclusions: MetS is associated with abnormal right ventricular and pulmonary artery hemodynamics, as shown by shorter PAAT and subclinical right ventricular diastolic dysfunction. Estimated pulmonary artery systolic pressures are higher in MetS and preclinical metabolic heart disease and raise the possibility that pulmonary hypertension contributes to the pathophysiology of metabolic heart disease.